2014
DOI: 10.1074/jbc.m113.507616
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal SplB Serine Protease Utilizes a Novel Molecular Mechanism of Activation

Abstract: Background: Activation of SplB protease requires precise N-terminal processing, but the molecular mechanism remains unknown. Results:The new N-terminal Glu-1 forms a distinctive H-bond network essential for full catalytic activity. Conclusion: Changes in protein dynamics rather than a direct effect on the active site are of crucial importance in SplB activation. Significance: A novel serine protease activation mechanism was uncovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 33 publications
4
23
0
Order By: Relevance
“…6a). This was similar to the zymogens of the staphylococcal SplB protease (Pustelny et al, 2014) and bovine trypsin (Fehlhammer et al, 1977), in which the spatial arrangement of the catalytic residues (Ser214, Asp102, His57 and Ser195; chymotrypsin numbering) in the zymogens was almost similar, but with slightly distorted or inadequately formed S1 pockets compared with the mature enzymes. Such an arrangement in the zymogen could also explain the complete absence of activity against the specific substrate (Fig.…”
Section: A Structural Perspective On Pro-esp Activationsupporting
confidence: 63%
“…6a). This was similar to the zymogens of the staphylococcal SplB protease (Pustelny et al, 2014) and bovine trypsin (Fehlhammer et al, 1977), in which the spatial arrangement of the catalytic residues (Ser214, Asp102, His57 and Ser195; chymotrypsin numbering) in the zymogens was almost similar, but with slightly distorted or inadequately formed S1 pockets compared with the mature enzymes. Such an arrangement in the zymogen could also explain the complete absence of activity against the specific substrate (Fig.…”
Section: A Structural Perspective On Pro-esp Activationsupporting
confidence: 63%
“…[26,27] Other MRSA biofilm gene clusters with changes in expression profiles due to HP-14 include: spl (serine proteases; [28] activated), opp (oligopeptide transporters; [29] activated), gap (glycolysis; [30] inhibited), arc (arginine deiminase; [31] inhibited), ure (urease; [32] inhibited), hem (heme biosynthesis; [33] inhibited), and an uncharacterized gene cluster containing dnaC (DNA synthesis and repair; [34] inhibited; see Figures 1 and 2 in the Supporting Information). Several gene clusters with unknown functions or lower levels of activation/inhibition in response to HP-14 are presented in the Supporting Information (for WoPPER details, see Tables 6 and 7).…”
mentioning
confidence: 99%
“…Proteolitic activity of SplE was routinely verified with zymography using b-casein as a substrate (Arvidson et al, 1973). SplB was expressed and purified as described previously (Pustelny et al, 2014). Mutants were generated by site directed mutagenesis, verified by sequencing and purified similarly to the wild type SplB.…”
Section: Star+methodsmentioning
confidence: 99%
“…It is unlikely that the observed conformation is induced directly by crystal-specific interactions (tight packing), since the closest adjacent molecule is more than 6 Å away from the discussed region and there is no indication of ordered solvent in the water channel between the two molecules. At the same time, however, the N terminus of SplE is involved in multiple interactions with an adjacent molecule, while it has been previously demonstrated that precise positioning of the N terminus influences the activity of SplB (Pustelny et al, 2014). Although this might suggest indirect influence of crystal packaging on the conformation of loop 1, we rather believe that the observed conformation constitutes a native arrangement and is related to a substrate-induced activation mechanism, as previously suggested for SplC (Popowicz et al, 2006) and analyzed in more detail in the discussion section.…”
Section: Substrate Preference Of Sple Extends Beyond P1 Residuementioning
confidence: 99%